Posisi dan Urgensi Bimbingan Konseling Dalam Praktik Pendidikan - Yenti Arsini; Khairunnisa Harahap; Saida Amini Thasfa (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study aims to determine the position and urgency of counseling guidance in educational practice. This research method uses literature review research methods (library research). Counseling guidance does have an important role and position for students. The role of guidance and counseling is very helpful in improving the quality of education. Because this guidance and counseling can help find solutions to problems that occur in the world of education. As it is well known that in educational activities in counseling guidance which is positioned as an integral part of the overall educational activities in schools in its implementation has several operational patterns, especially in the current situation where the function of schools or formal educational institutions is not only to equip students who are a pile of knowledge but also prepare students to meet the guidance of change and progress that occurs inÂ  community. So the position of counseling guidance in education is a forum or institution to accommodate and solve student problems that cannot be accommodated and resolved by educators.